Generalized spline spaces over T-meshes: Dimension formula and locally refined generalized B-splines - Bracco, Cesare; Lyche, Tom; Manni, Carla; Roman, Fabio; Speleers, Hendrik (Applied mathematics and computation, 2016)
Univariate generalized splines are smooth piecewise functions with sections in certain extended Tchebycheff spaces. They are a natural extension of univariate (algebraic) polynomial splines, and enjoy the same structural properties as their polynomial counterparts. In this paper, we consider generalized spline spaces over planar T-meshes, and we deepen their parallelism with polynomial spline spaces over the same partitions. First, we extend the homological approach from polynomial to generalized splines. This provides some new insights into the dimension problem of a generalized spline space defined on a prescribed T-mesh for a given degree and smoothness. Second, we extend the construction of LR-splines to the generalized spline context.